Penerapan Sistem Informasi Manajemen Keluarga Berencana Pada Badan Kependudukan Keluarga Berencana Daerah - Gatot Hery Djatmika; Asep Hendriyana (Universitas Mohammad Husni Thamrin, 2020)
Regional Population Family Planning Board is an institution / agency that functions to control the population by providing information on contraceptives to the community to form family planning. Family Planning is a government program designed to balance the needs of life and population. The family planning program is carried out by the government so that the family as the smallest unit of national life accepts the Norms of a Happy and Prosperous Small Family which is oriented towards balanced growth. To support this goal, it is necessary to collect data on fertile age couples. The fertile age couples data collection activity that was previously carried out manually is an administrative process as well as routine activities carried out. Based on the reality on the ground, the fertile age couples data collection which is carried out manually is deemed ineffective and inefficient. Therefore, it is necessary to implement a Family Planning Management Information System, among others, for online fertile age couples data collection with the aim of creating transparency in fertile age couples data and facilitating data collection on participants of fertile, targeted, and quality family planning couples. The place of research is the Regional Population Family Planning Board Curugkembar Sukabumi District. From the results of the application of the Family Planning Management Information System, it can be concluded that: The application of a Web-based Family Planning Management Information System at the Regional Family Planning Population Board, facilitates and speeds up data processing. The system also allows setting the service schedule and control. In designing a web-based Management Information System program, it minimizes the possibility of errors in the data entry process for fertile age couples on family planning. With the implementation of this Management Information System, delays in making reports will be minimized every month.